The Chloranthus sessilifolius genome provides insight into early diversification of angiosperms - Jianxiang Ma (Nature Portfolio, 2021)
Chloranthales remain the last lineage of core angiosperms that lacks a nuclear genome assembly. Here, the authors report the genome assembly of Chloranthus sesilifolius and show that both hybridization and incomplete lineage sorting may have contributed to the phylogenetic incongruities in the literature.